Consumer social network brand identification and personal branding. How do social network users choose among brand sites? - Wioleta Kucharska; Len Tiu Wright (Cogent Business & Management, 2017)
Brands' social networking sites (fan pages) are increasingly attracting the attention of scientists and managers intrigued by their potential application for brand value creation. The aim of this research is to understand better how users choose among social networking sites as an act of brand identification. The study presents a new model whose structure of identification drivers for social networking brand sites varies for customer brand identification in the real and virtual worlds. The presented model reveals that personal branding is a planned effect of brand identification and it is crucial for brand value creation in social networks.
Keywords: 650